Managing local knowledge about NBS in spatial planning. A group model building approach - Santoro, Stefania; Mastrodonato, Giulia; Camarda, Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Nature-based solutions (NBS) are increasingly adopted as measures for enabling climate change mitigation and adaptation, reducing flood risks and enhancing urban ecosystems. However, several barriers hinder the implementation of NBS in urban areas, in planning activities and strategies. These include the inadequacy of some existing methods based on hard and top-down approaches, the complexity and uncertainty associated with the network of citizens involved and the structuring of the knowledge deriving from that, in urban strategies. Local knowledge could help to understand the success or failure of actions designed only by expert knowledge. To this aim, this paper contributes to a current debate about methodological approaches to knowledge assessment to adopt in urban planning processes. Specifically, this paper proposes a Group Model Building approach for one of the activities carried out within the planning process for the Master Plan draft of the city of Brindisi, to support NBS implementation. The results, among others, highlight three important aspects: the importance of building a model to support the elicitation of participants' knowledge, the need to create a well-structured process leading to consensus, and the need to involve the young population in the participatory processes.